The study on the behaviour of plate girder with profiled web / Md. Hadli Abu Hassan - Abu Hassan, Md. Hadli (2006)
Engineers have long realized that corrugated webs enormously increase steel girders' stability against buckling and can result in very economical design. Recently, the new idea of combining the two profiled webs brought new issues of research. The objective of the research presented in this thesis is to investigate the behavior of steel girders with profiled web subjected to shear. Relative buckling modes are also discovered. The work includes experimental works and nonlinear finite element analyses, which includes the development of material and geometric finite element model, whose results are verified against the test results. All the tested specimens and the model were loaded under three point bending. At the same time, calculations are made to investigate their validity in analyzing this kind of girder. The detailed ultimate shear capacity and buckling modes of the girders subjected to different profiled web arrangement cases were studied. The three buckling modes have occurred in this investigation were local, zonal and global buckling mode. It was found that, within the parametric range studied in this thesis, the typical failure modes of the girder with profiled webs are initially in the local buckling mode which occurred either at the top, middle or bottom of the one corrugation fold. After reaching a peak load the buckling propagated to other folds which transformed to zonal or extended to a global buckling mode in a diagonal direction of tension field action beyond the peak load (post-buckling load) and gradually buckled due to crippling of the web and subsequently buckled till the flanges yielded vertically into the web. In the process of buckling, the load displacement relationship of the girder switched to a sudden and steep descending branch. The buckling can reduce the post-buckling shear capacity in the range of 30% to 50% of the ultimate shear capacity. However, the ultimate or post-buckling capacities of profiled web girder did not depend on their buckling mode. Comparison between experimental results and finite element results were satisfactory. Comparison of the ultimate shear capacities between corrugated web girders with the equivalent conventional girders, the ratios were up to 2.00 and 4.30 for singly and doubly webbed corrugated girders respectively.